Molecular Links between the Circadian Clock and the Cell Cycle. Issue 12 (29th May 2020) - Farshadi, Elham; van der Horst, Gijsbertus T.J.; Chaves, Inês
Abstract: Circadian control of cell division is well established in diverse organisms. Recent single-cell studies on mouse fibroblasts have shown that the circadian clock and cell cycle systems are robustly phase-coupled in a bidirectional manner. In healthy cells, coupling of clock and cell cycle results in timed mitosis and rhythmic DNA replication. However, little is known about the interplay between these two oscillators in cancer cells, which often display de-regulated cell proliferation and circadian gene expression. Here we review the molecular organization of the circadian clock and the cell cycle, as well as the reciprocal interaction between the circadian clock and the cell cycle in normal and in cancer cells. Understanding how the circadian clock and cell cycle are coupled in cancer cells will be instrumental to optimally take advantage of chronotherapy in cancer treatment, as efficiency of therapy benefits from asynchrony in timed mitosis between the host and the malignant cells in order to predict the optimal time of treatment. Graphical abstract: Unlabelled Image Highlights: The circadian clock and the cell cycle are tightly coupled and oscillate with the same frequency (1:1 coupling). Circadian clock genes regulate cell cycle check points and cell cycle progression. Expression of circadian clock genes is often dysregulated in cancer, and circadian disturbance predisposes to cancer. Differences in coupling between the circadian clock and the cell cycle in normal and cancer cells could be used to optimize cancer therapy (chronotherapy).